Secagem, armazenamento e validação de metodologia para teste de germinação de sementes de porta-enxertos de citros - Gonçalves, Maria Izabel Furst (2017)
Because of the importance as a rootstock, Cleopatra mandarin (Citrus reshni) seeds need to be preserved for medium and long terms. Thus, the objective was to study the drying and storage effect to classify its post-harvest behavior. This work objective was to develop and validate a methodology for seed germination tests of this species and of the rangpur lime (Citrus limonia), trifoliate (Poncirus trifoliata) and citrumelo (C. paradisix P.trifoliata) rootstocks. Seeds of C. reshni were desiccated at two speeds (RH=10±3% and 75±3%), determining the germination and activity of the antioxidant system catalase and superoxide dismutase enzymes (ARTICLE 1). In a second step, these seeds were submitted to drying (RH=10±3%) until the water contents of 24.2; 11.3 and 5.5% and, together with fresh seeds (36.9% w.b), stored in a cold room at 6±2°C for three months. The drier seeds were also stored at -20±2°C. Germination after drying and storage and embryo viability and vigor after storage were evaluated (ARTICLE 2). Various qualities of seeds were tested for light and temperatures (25, 30 and 35°C). Interlaboratory tests were then performed (ARTICLE 3). This study concluded that regardless of drying rate, C. reshni seeds were tolerant to desiccation, maintaining high germination even after drying up to 3% water content and that the catalase and superoxide dismutase enzymes activities were not good indicators of the drying immediate effect. In the second stage, the desiccation tolerance was confirmed and itn was verified that the storage of wetter seeds (36.9 and 24.2% w.b) at 6±2°C for three months was more adequate, highlighting the fresh stored seeds by vigor. In addition, drier C. reshni seeds (5.5% w.b.) are sensitive to storage, especially at negative temperatures (-20±2°C), revealing a closer behavior of intermediate seeds. With regard to the germination methodology, we concluded that: a) the Cleopatra mandarin, rangpur lime and citrumelo seeds germinate better at temperatures of 25 and 30°C and this latter temperature provided faster germination for rangpur lime seeds; b) very wet substrates are not suitable for paper roll testing; c) only the methodology for rangpur lime seeds obtained good repeatability, reproducibility variation coefficient and excellent repeatability and reproducibility (R&R) variation coefficient, and was considered valid for incorporation to the rules for seed analysis.